SWOT Analysis in Determining the Strategy for the Implementation of State-Owned Land Management Policy - Mario Bungaran Siregar; Dahyar Daraba; Faria Ruhana (Jurnal Penelitian Pendidikan, 2024)
The Directorate General of Higher Education, Research, and Technology (Ditjen Diktiristek), as one of the main units within the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), holds the responsibility as the Authorized User of State-Owned Assets (BMN), one of which is land. However, in its implementation, there are still various internal and external hindering factors that make the management of BMN in the form of land owned by Ditjen Diktiristek less than optimal. The research question is: what is the SWOT analysis of BMN land management at Ditjen Diktiristek, and what strategies should be formulated based on this analysis. The objective of this study is to describe and analyze the strategies needed to overcome obstacles in the implementation of BMN land management policies at Ditjen Diktiristek. The research method used is a qualitative research method with a descriptive approach, using data collection techniques obtained from a literature review. Furthermore, in analyzing the collected data, the researcher provides in-depth arguments and compares them using source triangulation to ensure the validity of the objective analysis. The research results show that there are four strategic issues in the policy of BMN land management at Ditjen Diktiristek, namely building cooperation with external parties, proposing budget increases, drafting detailed SOPs related to handling problematic land, and maximizing SAKTI and SIMAN as integrated information systems.